MENGGALI ALASAN DI BALIK ORIENTASI INDIVIDU NIAT KARIER KEWIRAUSAHAAN, APAKAH LITERASI DAN NIAT KEWIRAUSAHAAN MEMANG DIPERLUKAN? - Abdul Ahmad, Salwa Alya Putri (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The motivations driving individuals to pursue entrepreneurial careers and the significance of entrepreneurship education in fostering these intentions. The study reveals that various factors, such as personal aspirations, the desire for independence, the optimization of personal potential, and the flexibility offered by entrepreneurship, significantly influence students’ decisions to become entrepreneur. Additionally, the article emphasizes the vital role of entrepreneurship education in equipping individuals with essential skills, including business management, strategic planning, and marketing. This educational framework not only enhances creativity and innovation but also cultivates an entrepreneurial mindset that encourages risk-taking and resilience in the face of failure. Ultimately, the findings suggest that a synergistic relationship between intrinsic motivation and quality entrepreneurs capable of contributing meaningfully to the economy. Individual entrepreneurial orientation refers to thr personal attributes and behaviors that drive a person’s propensity to engage in entrepreneurial activites This orientation encompasses several key dimensions, including risk-taking, proactivity, and innovation. Individuals with a strong entrepreneurial orientation are often characterized by their willingness to embrace uncertainty and take calculated risks in pursuit of new opportunities. They exhibit a proactive approach, actively seeking out challenges and solutions rather than waiting for circumstances to change. Additionally, their innovative mindset allows them to think creatively, generating novel ideas and approaches that can lead to successful ventures. This orientation is influenced by various factors, including personal experiences, education, and environmental context. Ultimately, individuals with a robust entrepreneurial orientation are more likely to initiate and sustain entrepreneurial endeavors, contributing positively to economic growth and innovation within their communities. Kata kunci : orientasi kewirausahaan, literasi kewirausahaan dan niat kewirausahaan